Retreat of the Antarctic Ice Sheet During the Last Interglaciation and Implications for Future Change. Issue 17 (29th August 2021) - Golledge, N. R.; Clark, P. U.; He, F.; Dutton, A.; Turney, C. S. M.; Fogwill, C. J.; Naish, T. R.; Levy, R. H.; McKay, R. M.; Lowry, D. P.; Bertler, N. A. N.; Dunbar, G. B.; et al.
Abstract: The Antarctic Ice Sheet (AIS) response to past warming consistent with the 1.5–2°C "safe limit" of the United Nations Paris Agreement is currently not well known. Empirical evidence from the most recent comparable period, the Last Interglaciation, is sparse, and transient ice‐sheet experiments are few and inconsistent. Here, we present new, transient, GCM‐forced ice‐sheet simulations validated against proxy reconstructions. This is the first time such an evaluation has been attempted. Our empirically constrained simulations indicate that the AIS contributed 4 m to global mean sea level by 126 ka BP, with ice lost primarily from the Amundsen, but not Ross or Weddell Sea, sectors. We resolve the conflict between previous work and show that the AIS thinned in the Wilkes Subglacial Basin but did not retreat. We also find that the West AIS may be predisposed to future collapse even in the absence of further environmental change, consistent with previous studies. Plain Language Summary: Ice sheets can respond to climatic warming in complex ways, commonly only reaching a new state of balance many hundreds or even thousands of years after the initial change in climate has occurred. Here, we investigate how the Antarctic Ice Sheet (AIS) responded to a period of prolonged warmer‐than‐present climate that took place around 125, 000 years ago. At this time the global climate was only around 1–2°C above present, but geological records show that the global sea level was at least 6 m, or maybe even as much as 9–11 m, higher than today. Our study shows that around 4 m of this could have come from Antarctica. Our model agrees well with geological evidence of enhanced ice discharge both close to the ice sheet and further afield. Applying this model to the future our experiments suggest that the West AIS may already have been sufficiently destabilized to trigger a long‐term sea‐level contribution of up to 4 m, even without further greenhouse gas emissions. Key Points: We present data‐constrained simulations of the Antarctic Ice Sheet through the Last Interglaciation Our model predicts a maximum contribution to global mean sea level of 4 m at 126 ka BP Loss of much of the present‐day West Antarctic Ice Sheet is already committed under current climate